The Influence of Polymerization Type and Reinforcement Method on Flexural Strength of Acrylic Resin. (23rd March 2015) - Fonseca, Rodrigo Borges; Kasuya, Amanda Vessoni Barbosa; Favarão, Isabella Negro; Naves, Lucas Zago; Hoeppner, Márcio Grama
Abstract : The aim of this study was to evaluate the flexural strength of acrylic resin bars by varying the types of resin polymerization and reinforcement methods. Fourteen groups (N = 10 ) were created by the interaction of factors in study: type of resin (self-cured (SC) or heat-cured (HC)) and reinforcement method (industrialized glass fiber (Ind), unidirectional glass fiber (Uni), short glass fiber (Short), unidirectional and short glass fiber (Uni-Short), thermoplastic resin fiber (Tpl), and steel wire (SW)). Reinforced bars (25 × 2 × 2  mm) were tested in flexural strength (0.5 mm/min) and examined by scanning electron microscopy (SEM). Data (MPa) were submitted to factorial analysis, ANOVA, and Tukey and T-student tests (a = 5 %) showing significant interaction (P = 0.008 ), for SC: Uni ( 241.71 ± 67.77 ) a, Uni-Short ( 221.05 ± 71.97 ) a, Ind ( 215.21 ± 46.59 ) ab, SW ( 190.51 ± 31.49 ) abc, Short ( 156.31 ± 28.76 ) bcd, Tpl ( 132.51 ± 20.21 ) cd, Control SC ( 101.47 ± 19.79 ) d and for HC: Ind ( 268.93 ± 105.65 ) a, Uni ( 215.14 ± 67.60 ) ab, Short ( 198.44 ± 95.27 ) abc, Uni-Short ( 189.56 ± 92.27 ) abc, Tpl ( 161.32 ± 62.51 ) cd, SW ( 106.69 ± 28.70 ) cd, and Control HC ( 93.39 ± 39.61 ) d . SEM analysis showed better fiber-resin interaction for HC. Nonimpregnated fibers, irrespective of their length, tend to improve fracture strength of acrylics.